Vegetative and endocrine predictors of individual immune responses to adaptogenic balneotherapy - Struk, Zoryana; Mel’nyk, Oksana; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2020)
Background. Earlier four variants of the immune responses to adaptogenic balneotherapy have been identified. All four variants of immune responses are virtually unmistakably predicted by a set of 20 predictors including 12 immune blood parameters and one saliva parameter, 4 information parameters, 2 fecal microbiota parameters as well as erythrocyturia. The purpose of this study is to search for predictors of immune responses among the registered parameters of the autonomic nervous and endocrine systems. Material and methods. The object of observation were 34 men and 10 women aged 24-70 years old, who came to the Truskavets’ spa for the treatment of chronic pyelonephritis combined with cholecystitis in remission. We determined them the HRV parameters and plasma levels of principal adaptation Hormones: Cortisol, Testosterone and Triiodothyronine. Results. Discriminant analysis revealed that constellation 8 HRV and 5 Endocrine parameters as well as Gender of the patient predicts the nature of the immune response with an accuracy of 90,9%. Conclusion. The previously revealed variety of immune responses to adaptogenic balneotherapy is quite strictly conditioned by the initial state of the neuroendocrine-immune complex and microbiota as well as the sex of patients.